Sildenafil citrate therapy in absent end diastolic flow in umbilical artery in an early onset fetal growth restriction (FGR) fetus - Choudhary, Rana A.; Patrawala, Khyati; Desai, Kavita; Ganla, Kedar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Fetal growth restriction (FGR), a pregnancy complication still poses as a challenge for obstetricians worldwide. This is because of its association with severe morbidity and mortality outcomes. Obstetrical management becomes a dilemma in determining the optimal time of delivery and weighing the risks of prematurity against the risks of a potentially hostile intrauterine environment. There may be placental insufficiency characterized by insufficient blood flow in the umbilical artery. This is termed as abnormal umbilical artery flow with absent or reversed end diastolic flow on Doppler USG. Worsening of this condition demands an earlier delivery of the fetus. Authors report a case of structurally normal foetus showing severe early onset FGR with absent end diastolic flow in umbilical artery on Doppler, which was managed using vaginal Sildenafil citrate. Sildenafil citrate led to improvement in uterine artery and umbilical artery Doppler parameters; thereby improving the utero-placental blood flow with a favorable fetal outcome at delivery. The gestation was prolonged by 51 days. Thus, Sildenafil citrate can be used as promising agent in early onset FGR in selected cases.